Vulnerability to Oil Price Increases : A Decomposition Analysis of 161 Countries - Bacon, Robert; Kojima, Masami (World Bank, Washington, DC, 2014)
This paper examines the levels of and changes in vulnerability to oil price increases between 1996 and 2006 in 161 countries for which data are available. Vulnerability defined here as the ratio of the value of net oil imports to gross domestic product (GDP) rises if oil consumption increases and oil production decreases per unit of GDP. By comparing the level of vulnerability of different economies at a point in time, those that are particularly vulnerable to oil price increases can be highlighted. This enables consideration of the factors (variables) that help determine the magnitude of vulnerability. Over time economies change in ways that may make them more vulnerable to oil price increases or less so, and the change in vulnerability will be related to changes in the underlying variables. The analysis this paper uses is a starting point for linking these factors. The study also examined changes in vulnerability by subdividing the period under review into two sub-periods, 1996-2001 and 2001-6. The oil price increase during the first sub-period was small, and correspondingly the change in vulnerability was also limited. The change in vulnerability was greater during the second sub-period, which saw a 2.5-fold price increase in nominal U.S. dollars. This paper highlights the role of changes in the oil share of energy and of energy intensity, both of which can be influenced by government policies, and also by oil production, which, even though it is largely a function of geology, can also be affected by a country's upstream fiscal, contractual, and regulatory frameworks.